AAN Controller With Adaptive Gain for Upper Limb Exoskeleton - Jixin Dong; Zhiwei Jia; Erwei Li; Qipeng Lv (IEEE Access, 2024)
In this paper, the problem of the assist-as-needed (AAN) control of the upper limb exoskeleton is studied. Due to the complexity of the upper limb exoskeleton structure and driving mode, the control parameters of the equipment need to be adjusted to obtain satisfactory control performance. This paper presents an adaptive gain control method based on AAN. Through the dynamic gain adjustment mechanism, the system can adjust the control force in real-time to avoid excessive or insufficient auxiliary force. It can overcome the problem that traditional adaptive cannot identify dynamically changing parameters efficiently, and effectively avoid the overshoot and oscillation problems of high-gain adaptive, and do not need to obtain unknown disturbance information in complex models. The method adopts the on-demand auxiliary strategy to realize the self-adaptation of the auxiliary force and mode adjustment, which ensures the comfort, safety and effectiveness in the rehabilitation process. Through simulation experiment and comparison with the latest AAN controller, it can be seen that the controller has good anti-jamming effect and adaptive adjustment ability to auxiliary force under unknown interference.